Why you should eat beans - Kalemera, Sylvia Monica; Kasubiri, Fadhili; Onyango, Patricia; Kadege, Edith; Rubyogo, Jean-Claude (2022)
This poster infographic outlines why all humans should eat beans. Beans provide protein, fiber, folate, iron, potassium and magnesium while containing little or no total fat, trans-fat, sodium and cholesterol.